Trinity and truth - Marshall, Bruce (Cambridge studies in Christian doctrine, 2000)
Two closely related questions receive distinctively theological answers in this study: What is truth? and How can we tell whether what we have said is true? Bruce Marshall proposes that the Christian community's identification of God as the Trinity serves as the key to a theologically adequate treatment of these questions. Professor Marshall argues on trinitarian grounds that the Christian way of identifying God ought to have unrestricted primacy when it comes to the justification of belief, and he proposes a trinitarian way of reshaping the concept of truth. Direct engagement with the current philosophical debate about truth, meaning and belief (in Quine and others) suggests that a trinitarian account of epistemic justification and truth is also more philosophically compelling than the approaches generally favoured in modern theology, as exemplified by Schleiermacher, Ritschl, Rahner and others. Marshall offers a contemporary way of conceiving of the Christian God as 'the truth'.